Methods Of Applying Herbicides Against Weeds Around The Field (Texas Journal of Agriculture and Biological Sciences, 2025)
The article identifies the harmful effects of herbicides on weeds around the field by determining the degree of herbicide effect for each species, specifically determining the dosage of preparations based on weed species and development conditions, and recommending control measures